Women and Sustainable Development in Africa: Issues and Challenges from Nigeria (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Globally, crave for sustainable development and increasing women participation in governance have been on unabated. This is premised on the belief that sustainable development is attainable where and when there is good governance and gender justice. Making use of library research and content analysis methodologies, the paper detailed in a systematic manner the missing link in sustainable development in Africa with particular emphasis on Nigeria. It analyses the current practice ofsextortion among the women in decision- making processes and leadership at the national, state and local levels and its impact on development. More so, the paper discusses the conditions that facilitate womens representation in decision-making processes within the context of the current socio-economic and political transformations. It also examines the linkages between womens presence in critical decision-making positions and sustainable development. The paper contends that most states in Africa are yet to attain development to be sustained. It blames the African leaders and the patriarchal states for the precarious pace at which the region develops. The paper concludes that sustainable development will remain a pie in the sky in Africa for as long as greed, self-centeredness and emperornic disposition of African leaders as well as mass poverty and infrastructural decay continue.